Phantom Limb Pain Rating Scale: A Scale Development Study - KATRAN, HAMDİYE BANU (My University, 2024)
Purpose: The aim of this study was to develop a valid and reliable scale to evaluate and measure phantom limb pain. Material and Methods: This study, which was designed in a methodological type, was conducted with a total of 258 patients. A demographics form and a draft scale developed by the research authors were used to collect the study data. Kuder-Richardson Formula 20 was used to provide descriptive statistics and reliability analyses for the study data. Exploratory Factor Analysis was used in the development of the phantom limb pain rating scale, and Reliability and Confirmatory Factor Analysis were used for the study’s validity and reliability evaluations. Results: The Kuder-Richardson 20 value, which shows the internal consistency of the questions of the 16-item the rating scale, was found to be 0.921. The total score of the rating scale ranged from 1 to 16, with an average of 11.19±4.94. It was determined that the fit criterias and corrected chi-square values showed acceptable fit, and that the scale was both statistically significant and valid (p=0.001; p<0.01). Conclusion: The self-reported scale developed in this study was found to be a reliable and valid measurement tool for evaluating phantom limb pain in affected patients. Keywords: Amputation, Pain Measurement, Phantom limb pain, Scale, Pain.
Keywords: Hemşirelik; Cerrahi Hastalıkları Hemşireliği; Sağlık Bilimleri; Nursing; Surgical Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Amputation; Pain Measurement; Phantom limb pain; Scale; Pain